Chinese Alchemy - Pregadio, Fabrizio (Oxford Bibliographies in Chinese Studies, 2020)

Daoism and Divination - Pregadio, Fabrizio (Handbook of Prognostication and Prediction in China, 2021)

Dictionary of Taoist Internal Alchemy - Pregadio, Fabrizio (Brill, 2025)
This dictionary offers a unique perspective on the vast and varied terminology of Taoist Internal Alchemy (Neidan). Drawing on major original texts and premodern lexicons, it provides translations, definitions, and usage examples for over a thousand terms common throughout the tradition. A comprehensive index of English equivalents allows readers to easily locate the corresponding Chinese terms. Beyond serving as a reference for those reading, studying, or translating Neidan texts, the dictionary's entries offer glimpses into the rich imagery and poetic language of Internal Alchem

Great Clarity: Daoism and Alchemy in Early Medieval China - Pregadio, Fabrizio; et al. (Stanford University Press, 2006)
This is the first book to examine extensively the religious aspects of Chinese alchemy. Its main focus is the relation of alchemy to the Daoist traditions of the early medieval period (third to sixth centuries). It shows how alchemy contributed to and was tightly integrated into the elaborate body of doctrines and practices that Daoists built at that time, from which Daoism as we know it today evolved. The book also clarifies the origins of Chinese alchemy and the respective roles of alchemy and meditation in self-cultivation practices. It contains full translations of three important medieval texts, all of them accompanied by running commentaries, making available for the first time in English the gist of the early Chinese alchemical corpus. Translated into Chinese by Han Jishao 韓吉紹 as Taiqing: Zhongguo zhonggu zaoqi de daojiao he liandanshu 太清 － 中国中古早期的道教和炼丹术 (Jinan: Qi Lu shushe, 2016)<br

Seeking Immortality in Ge Hong's Baopuzi neipian - Pregadio, Fabrizio (Dao Companion to Xuanxue 玄學 (Neo-Daoism), 2020)

Superior Virtue, Inferior: A Doctrinal Theme in the Works of the Daoist Master Liu Yiming (1734-1821) - Pregadio, Fabrizio (T'oung Pao, 2014)

Taoist Internal Alchemy: An Anthology of Neidan Texts - Pregadio, Fabrizio; et al. (Golden Elixir Press, 2019)
This anthology presents complete or partial translations of sixteen important works belonging to the Taoist tradition of Neidan, or Internal Alchemy. While the selections are far from covering the whole field of Neidan—a virtually impossible task, given its width and variety—they are representative of its main lineages and branches. Texts have been selected in this perspective and are arranged chronologically, in order to provide an overview not only of Neidan, but also of the history of its discourses and practices. Four of the sixteen texts are integrally translated. Six texts and two commentaries are translated here (entirely or partially) for the first time into English. The book is concluded by several tables and by an index of the main terms.<br

The Alchemical Body in Daoism - Pregadio, Fabrizio (Journal of Daoist Studies, 2021)

The Encyclopedia of Taoism - Pregadio, Fabrizio; et al. (Routledge, 2008)
Contains about 800 articles written by 46 contributors from the USA, Canada, England, France, Germany, Italy, Australia, China, Taiwan, and Japan. Prized as “Outstanding Reference Source” by the American Library Association in 2009.<br

The Man-Bird Mountain: Writing and Revelation in Early China - Pregadio, Fabrizio (International Journal of Divination and Prognostication, 2020)